PHYSICO-CHEMICAL AND SENSORY CHARACTERISTICS OF YOUNG COCONUT (Cocos nucifera L.) SHEET JAM WITH A COMBINATION OF TYPES OF SWEETENERS - Sari, Nopita; Lestari, Oke Anandika; Saputri, Nur Endah (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2026)
Sheet jam is a modification of spreadable jam which has a sheet shape that fits the surface of the bread. This research aims to evaluate the effect of replacing granulated sugar with alternative sweeteners, fructose syrup, kelulut honey, and liquid palm sugar, on the physicochemical and sensory characteristics of young coconut meat sheet jam. This research used a Randomized Block Design (RAK) with four treatments (P0: granulated sugar, P1: liquid fructose syrup, P2: kelulut honey, P3: liquid palm sugar) and six replications, so there were 24 experiments. The data obtained will be analyzed using Analysis of Variant (ANOVA) then followed by the Honestly Significant Difference (BNJ) test at the 5% level. Meanwhile, the hedonic test data was tested using the Kruskal Wallis test. The results showed that the formulation with fructose syrup provided the best physicochemical characteristics for young coconut meat sheet jam, with a water content of 8.30%, reducing sugar 26.77%, color L 30.78%, color a 8.17%, and color b 11.52%. Sensorily, jam sweetened with fructose syrup obtained the best hedonic scores for taste (3.80: like), aroma (3.66: like), color (4.00: prefer), and texture (4.23: prefer like)